Synthesis, anticancer and FGFR1 inhibitory activity of isoindolo isoindolo[2,1-a][1,2,4]triazino[2,3-c]quinazoline derivatives - Voskoboynik, O. Yu.; Starosyla, S. A.; Protopopov, M. V.; Volynets, H. P.; Shyshkina, S. V.; Yarmoliuk, S. M.; Kovalenko, S. I.; Воскобойнік, Олексій Юрійович; Старосила, С. А.; Протопопов, М. В.; Волинець, Г. П.; Шишкіна, С. В.; et al. (ТДМУ, 2016)
presented manuscript describes the synthesis, antitumor and fgfr1 inhibitory activity of novel isoindolo[2,1-a] [1,2,4]triazino[2,3-c]quinazolines. it was shown that mentioned above substances may be prepared by interaction of 3-(2-amino-3-r2-5-r3-phenyl)-6-r1-1,2,4-triazin-5(2h)-ones with 2-formylbenzoic and 6-formyl-,3-dimethoxybenzoic (opianic) acids in acetic acid. it was shown that proper 2-(2-oxo-3-r-6,7-dihydro-2h-[1,2,4]triazino[2,3-c]quinazolin- 6-yl)benzoic acids (or corresponded dimethoxysubstituted analogues) may be considered as intermediates of the reaction. Spectral properties of synthesized compounds were studied, it was shown that protons in position 8 were observed at low feld as result of the presence of hydrogen bond between hydrogen at position 8 and oxygen at position 10. the anticancer assay data allowed to identify synthesized compounds as promising antitumor agents. the fgfr 1 inhibitory activity of synthesized compounds was detected and docking study aimed to the evaluation of mentioned action was conducted.
Синтез, протиракова та FGFR1 інгібуюча активність похідних ізоіндоло[2,1-a][1,2,4]триазино[2,3-c]хіназоліну
Keywords: isoindoles; triazines; quinazolines; anticancer activity; FGFR1 inhibitory activity; docking